Art and Activism; Empowering Batik Skills for Disabilities by Batik Contemporary Artisan - Cahyani, Isma Awal Fitroh (Universitas Negeri Medan, 2024)
ABSTRACTThe current trend of artists, both individually and collectively, is to try to carry out activism-based art practices as an effort to explore the role of the artist in the community that supports them. In craft art, there is a term Craftivism which was first discovered by a craftsman Betsy Greer in 2007. An actor/activist in Sukabumi City, a craftsman and owner of the Batik Lokatmala production house named Fonna Melania, presents typical Sukabumi batik motifs to bring sustainable benefits to the community and the surrounding environment, craftsmen try to respond to social problems that are present in their environment using batik as a method. Namely the existence of people with disabilities who do not have the opportunity to work, craftsmen try to invite and offer training as well as work, namely batik. Until collaborating with the Sentra PHALA MARTA Foundation (social rehabilitation center), the aim is to increase the skills of people with disabilities. This research is the result of an analysis of an art movement and activism carried out by a batik craftsman in solving problems that are present in his environment. Using the Craftivism analysis method by Alyce McGovern, there are three aspects that need to be considered, the first aspect is the personal aspect of batik craftsmen who try to respond to social problems in their environment, the second aspect is the Lokatmala Batik community which is led directly by craftsmen in creating an ecosystem of relations/collaboration between craftsmen and people with disabilities in the production process at the Lokatmala batik house, and the third aspect is politics (power), namely how craftsmen present solutions, make statements and take a stand on problems in their social environment while fighting for change. The activism fought for by craftsmen through batik art is carried out for the purpose of change for the better, improving the standard of living and welfare of disabled groups in their social environment. ABSTRACTThe current trend of artists, both individually and collectively, is to try to carry out activism-based art practices as an effort to explore the role of the artist in the community that supports them. In craft art, there is a term Craftivism which was first discovered by a craftsman Betsy Greer in 2007. An actor/activist in Sukabumi City, a craftsman and owner of the Batik Lokatmala production house named Fonna Melania, presents typical Sukabumi batik motifs to bring sustainable benefits to the community and the surrounding environment, craftsmen try to respond to social problems that are present in their environment using batik as a method. Namely the existence of people with disabilities who do not have the opportunity to work, craftsmen try to invite and offer training as well as work, namely batik. Until collaborating with the Sentra PHALA MARTA Foundation (social rehabilitation center), the aim is to increase the skills of people with disabilities. This research is the result of an analysis of an art movement and activism carried out by a batik craftsman in solving problems that are present in his environment. Using the Craftivism analysis method by Alyce McGovern, there are three aspects that need to be considered, the first aspect is the personal aspect of batik craftsmen who try to respond to social problems in their environment, the second aspect is the Lokatmala Batik community which is led directly by craftsmen in creating an ecosystem of relations/collaboration between craftsmen and people with disabilities in the production process at the Lokatmala batik house, and the third aspect is politics (power), namely how craftsmen present solutions, make statements and take a stand on problems in their social environment while fighting for change. The activism fought for by craftsmen through batik art is carried out for the purpose of change for the better, improving the standard of living and welfare of disabled groups in their social environment.